THU0353 Change in mri structural lesions in the sacroiliac joint after two years of etanercept therapy in comparison to a contemporary control cohort in non-radiographic axial spondyloarthritis. (15th June 2017) - Maksymowych, WP; Dougados, M; Lambert, RG; Landewe, R; Molto, A; Claudepierre, P; Hooge, M de; Bonin, R; Bukowski, JF; Jones, H; Logeart, I; Pedersen, R; et al.
Abstract : Background: Demonstrating a structural effect of TNF inhibitors in axial SpA (axSpA) is challenging. Objectives: To compare 2 yrs of structural lesion changes on T1W MRI in the sacroiliac joints (SIJ) of pts receiving etanercept (ETN) in a clinical trial to similar pts not receiving biologics in a cohort study. Methods: Pts had recent onset non-radiographic (nr)-axSpA fulfilling ASAS criteria. Study group: pts receiving ETN 50 mg once weekly for 2 yrs in EMBARK (NCT01258738 ). Control group: pts in a longitudinal cohort study not receiving biologics for 2 yrs (DESIR, NCT01648907 ). Outcome measure: change in structural lesions of erosion, backfill, fat metaplasia, and ankylosis. MRI images were read by 3 experienced readers unaware of image chronology and pt group, using the SpondyloArthritis Research Consortium of Canada SIJ Structural Score (SSS). 1 For each group, differences were calculated between percentages of patients experiencing increases and decreases in structural lesion scores over 2 yrs. Treatment effect was analyzed without and with adjustment for the baseline (BL) covariates of sex, symptom duration, smoking status, HLA-B27 status, ASDAS-CRP, SPARCC MRI SIJ score, and SIJ radiography score. Results: At BL, pts with MRI images in the control (DESIR, N=76) and ETN (EMBARK, N=162) cohorts differed significantly in symptom duration, smoking status, ASDAS-CRP and SPARCC MRI SIJ score. The table presents structural lesion changes on MRI. The mean difference between control and ETN was significant for erosion (table). Figure shows cumulative probability plot. Conclusions: This analysis confirms the slow rate of structural lesion progression in the SIJ over 2 yrs in nr-axSpA and suggests a lower rate of progression with ETN than without a TNF inhibitor. References: Maksymowych WP, et al. J Rheumatol. 2015;42:79–86. Disclosure of Interest: W. P. Maksymowych Grant/research support from: AbbVie, Pfizer, Sanofi, Consultant for: AbbVie, Amgen, Eli Lilly, Janssen Pharmaceutica, L.P, Novartis, Pfizer, Sanofi, UCB, M. Dougados Grant/research support from: Pfizer, Abbvie, UCB, Merck, Lilly, Sanofi, Consultant for: Pfizer, Abbvie, UCB, Merck, Lilly, Sanofi, R. G. Lambert Consultant for: Bioclinica, R. Landewe Grant/research support from: Abbott, Amgen, Centocor, Novartis, Pfizer, Roche, Schering-Plough, UCB, Wyeth, Consultant for: Abbott/Abbvie, Ablynx, Amgen, Astra-Zeneca, BMS, Celgene, Janssen (formerly Centocor), Galapagos, GSK, Novartis, Novo-Nordisk, Merck, Pfizer, Roche, Schering-plough, TiGenix, UCB, Wyeth, Employee of: Is a director of Rheumatology Consultancy BV, which is registered company under Dutch law, A. Molto Grant/research support from: Pfizer, UCB, Consultant for: Abbvie, BMS, MSD France- Merck, Pfizer, UCB, P. Claudepierre Grant/research support from: Pfizer, Roche-Chugai, MSD, Consultant for: Abbvie, BMS, Celgene, Janssen, Novartis, Merck, Pfizer, Roche, UCB, M. de Hooge: None declared, R. Bonin Shareholder of: Pfizer, Employee of: Pfizer, J. Bukowski Shareholder of: Pfizer, Employee of: Pfizer, H. Jones Shareholder of: Pfizer, Employee of: Pfizer, I. Logeart Shareholder of: Pfizer, Employee of: Pfizer, R. Pedersen Shareholder of: Pfizer, Employee of: Pfizer, A. Szumski Employee of: InVentiv Health, B. Vlahos Shareholder of: Pfizer, Employee of: Pfizer, D. van der Heijde Consultant for: AbbVie, Amgen, Astellas, AstraZeneca, BMS, Boeringer Ingelheim, Celgene, Daiichi, Eli-Lilly, Galapagos, Gilead, Janssen, Merck, Novartis, Pfizer, Regeneron, Roche, Sanofi, UCB, Employee of: Director of Imaging Rheumatology bv.